Development of A Web-Based Integrated Daycare Child Care Application at The Ministry of Foreign Affairs - Wulandari, Rani Ika; Sulistyanto, Agus; Sianipar, Anton Zulkarnain (Jurnal Teknologi Informatika dan Komputer, 2025)
Daycare is a child care center (TPA) or childcare facility that is carried out in groups, usually held during regular working hours. Many parents are busy working outside the home, for parents who already have children will need help in caring for their children. Childcare Centers (TPA) become a means to replace family during periods when parents are working or other needs. Based on the questionnaire data obtained, it is known that parents have difficulty in finding childcare centers and information. Childcare centers are one form of early childhood education, where children will be cared for, looked after, and educated. However, the lack of information regarding Childcare Centers (TPA), many parents bring their children to their workplaces. These childcare centers are intended for parents who are busy working and have difficulty caring for their children. This study aims to build a Web-based application that can help parents in finding information about childcare centers. The design method used is the prototype method. This Web-based system and was tested using the Black Box testing method. The results of this study indicate that this system can help parents and childcare centers, and this system works according to the expected functions.